Off‐label underdosing of four individual NOACs in patients with nonvalvular atrial fibrillation: A systematic review and meta‐analysis of observational studies. (6th June 2022) - Sang, Chuanlan; Chen, Jiming; Sun, Junyi; Lai, Yuhui; Liu, Xiao; Zhu, Wengen
Abstract: Background: Although several meta‐analyses have examined the effects of off‐label underdosing of nonvitamin K antagonist oral anticoagulants (NOACs) compared with their recommended doses in patients with atrial fibrillation (AF), they combined different kinds of NOACs in their primary analyses. Herein, we first conducted a meta‐analysis to separately assess the effects of off‐label underdosing versus on‐label dosing of four individual NOACs on adverse outcomes in the AF population. Methods: The PubMed and Embase database were systemically searched until November 2021 to identify the relevant studies. Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were pooled by utilizing a random‐effects model. Results: A total of nine studies with 144, 797 patients taking NOACs were included in the meta‐analysis. In the pooled analysis, off‐label underdosing of rivaroxaban was related to an increased risk of stroke or systemic embolism (HR = 1.31, 95% CI 1.05–1.63; p  = .02), whereas off‐label underdosing of apixaban was associated with a higher risk of all‐cause death (HR = 1.21, 95% CI 1.05–1.40; p  = .01). When comparing off‐label underdosing versus on‐label dosing of dabigatran or edoxaban, no differences were found in the primary and secondary clinical outcomes. Conclusion: Off‐label underdosing of rivaroxaban may increase the risk of stroke or systematic embolism, whereas off‐label underdosing of apixaban may heighten the incidence of all‐cause death.